Komunikasi Persuasif Orang Tua pada Anak Remaja Broken Home - Patmaningsih, Wahyu (Dimar Jaya Publishing, 2023)
This research discusses the process of persuasive communication between parents for broken home teenagers in Krikilan Village, Driyorejo District, Gresik Regency. The aim of this research is to determine and describe the persuasive communication process of parents for broken home teenagers in Krikilan Village, Driyorejo District, Gresik Regency. This research uses descriptive qualitative methods. The research results show that, first, parents give a good impression so that broken home children feel cared for by their parents, so that parents can give advice for the good of their children. Second, parents are able to package messages in an interesting way so that children do not feel advised when communicating, ultimately children feel that this advice is a necessity for them so they are determined to change for the better. Third, parents must try to make broken home children feel comfortable when they are at home. This condition is needed so that children can feel at home and parents can provide good advice